Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbasis Simulasi PhET Terhadap Minat Belajar Dan Pemahaman Konsep Peserta Didik Pada Materi Gerak Harmonik Sederhana - Stefania Wilfrida Novianty Oke; Claudia Mariska M. Maing; Rosenti Pasaribu (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2023)
This research aims to 1) Knowing the guided inquiry learning model based on PhET simulation affects learning interest 2) Knowing the guided inquiry learning model based on PhET simulation affects students' concept understanding. The research design used is One-Group Pretest-Posttest Design. The sampling used is saturated sampling. The sample in this study were students of class X IPA SMA Swasta Santa Familia Sikumana which amounted to 24 people. The instruments used in the study were lesson plans, student worksheets, student teaching materials, learning interest questionnaires and concept understanding test questions. The results of the study concluded that there was an effect of guided inquiry learning model based on PhET simulation on students' interest in learning with a significant value of 0.014 smaller than 0.05 (0.014 <0.05). And there is an effect of guided inquiry learning model based on PhET simulation on students' concept understanding with a significant value of 0.000 smaller than 0.05 (0.000<0.05).